Using Visual Modeling Tools to Reach Students with Learning Disabilities - Hord, Casey; Gregson, Susan A.; Walsh, Jennifer B.; Marita, Samantha (Ohio Journal of School Mathematics, 2018)
Teachers can use electronic visual modeling tools to help students with learning disabilities visualize and understand mathematical concepts such as proportions, dilations, and scale factors. In this article, the authors describe strategies for using static and dynamic visuals for supporting the memory and processing of students with learning disabilities as they engage in challenging mathematics.